Privatizing Uncertainty and Socializing Risk: Indigenous Legal and Economic Leverage in the Federal Trans Mountain Buy-Out ... : خصخصة عدم اليقين ومخاطر التنشئة الاجتماعية: الرافعة القانونية والاقتصادية للسكان الأصليين في عملية الشراء الفيدرالية عبر الجبال ... - Shiri Pasternak; Nicole Schabus (OpenAlex, 2023)
[From Introduction]: "In an interview in early-September 2018 shortly after the federal buy-out of the Trans Mountain Pipeline Expansion Project (TMEP), Prime Minister Justin Trudeau proclaimed that this project would be dead if it were not for the higher risk tolerance of the federal government compared to that of previous owner, Kinder Morgan, Inc. (KM). In other words, the federal government could guarantee completion where a private corporation had failed to make the project viable – perhaps even because the project no longer needed to be economically viable to succeed. This statement of the sitting Prime Minister is troubling for many reasons, central among which because he implies that governments have a higher risk tolerance vis-à-vis abrogating Aboriginal title and rights, when indeed they have a constitutional obligation to maintain them and the honour of the Crown. Opposition to the pipeline, led by First Nations and environmental groups, was after all one of the reasons KM cited for selling off ... : [من المقدمة]: "في مقابلة أجريت في أوائل سبتمبر 2018 بعد فترة وجيزة من الاستحواذ الفيدرالي على مشروع توسيع خط أنابيب ترانس ماونتن (TMEP)، أعلن رئيس الوزراء جاستن ترودو أن هذا المشروع كان سيموت لولا تحمل الحكومة الفيدرالية لمخاطر أعلى مقارنة بمالكها السابق، كيندر مورغان (KM). وبعبارة أخرى، يمكن للحكومة الفيدرالية أن تضمن الإكمال عندما تفشل شركة خاصة في جعل المشروع قابلاً للتطبيق – ربما حتى لأن المشروع لم يعد بحاجة إلى أن يكون قابلاً للتطبيق اقتصاديًا لتحقيق النجاح. إن بيان رئيس الوزراء الحالي مقلق لأسباب عديدة، من بينها أنه يشير إلى أن الحكومات لديها قدرة أكبر على تحمل المخاطر فيما يتعلق بإلغاء حقوق الشعوب الأصلية وحقوقها، في حين أن عليها بالفعل التزامًا دستوريًا بالحفاظ عليها وشرف التاج. كانت معارضة خط الأنابيب، بقيادة الأمم الأولى والمجموعات البيئية، بعد كل شيء أحد الأسباب التي ذكرتها إدارة المعرفة لبيع هذا الأصل. تنطبق الالتزامات الدولية المتعلقة بالبيئة والسكان الأصليين وحقوق الإنسان مباشرة على الحكومات، لذلك إذا كان هناك أي شيء، فيجب على حكومة كندا الالتزام بتنفيذ معايير أعلى من الصناعة ". ...